CIPP-Based Evaluation of Physical Education, Sports, and Health Learning Implementation in a Vocational Secondary School - Muhammad Ghaluh; Eval Edmizal; Yendrizal Yendrizal; Kristian Burhan (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
Physical Education, Sports, and Health (PJOK) in vocational high schools often occupies a complementary role despite its important contribution to students' physical, social, and psychological development. This study evaluates the implementation of PJOK learning at SMKN 6 Padang, Indonesia, using Stufflebeam's Context, Input, Process, and Product (CIPP) evaluation model. A descriptive design was employed with a population of 997 Grade X and XI students and PJOK teachers. A sample of 90 students was selected through stratified random sampling using the Slovin formula (d = 0.1). Data were collected through validated Likert-scale questionnaires (teacher reliability = 0.940; student reliability = 0.790) and semi-structured interviews with three PJOK teachers, then analyzed using descriptive percentage analysis. The findings indicate that 78.9% of students rated PJOK implementation as